OPTIMALISASI IMPLEMENTASI BUDAYA RELIGIUS DI SEKOLAH DASAR ISLAM TERPADU AL RAHBINI GONDANGLEGI - ilun lailatul habibah; Aan Fardani; Sumarno Aziz (EBTIDA': Jurnal Pendidikan Dasar Islam, 2021)
This research departs from a thought and hope about the importance of character education in order to produce a generation of religious and morality. Character building is prioritized from an early age, and entering elementary school students are not only colored by the world of play, but also aspects of social responsibility. The process of development toward maturity sometimes does not always run smoothly in the direction of the potential, expectations and values ​​that it holds. So, it is important to equip students with the values ​​of meaningfulness of life, so that a mature and superior personality is formed. The purpose of this study was to understand the implementation of the program to improve religious culture and to describe the impact of the success of religious culture on the character of citizens at SD IT Al Rahbini Gondanglegi. This research uses a descriptive qualitative research approach. Data collection techniques carried out by (1) interviews, (2) observations, and (3) documentation. Data were analyzed by analysis of the Miles and Hubberman model consisting of data collection, data reduction, data display and conclusion. Checking the validity of the data is done by testing the credibility, dependability, and confirmability. The results of this study indicate that (1) The religious culture improvement program developed in can be grouped into several programs, namely the daily, weekly, monthly, yearly activity program, and the development of the Islamic Religious Education curriculum. (2) The impact of the application of religious culture on the character of school members includes the creation of a culture of greeting each other when meeting, mutual help, discipline, strong brotherhood,. decreasing the number of violations, increasing discipline, increasing students' understanding and knowledge of religious teachings, building mutual respect and appreciation between fellow teachers and other employees, better levels of teacher discipline and growing enthusiasm and curiosity about religion.